Critical studies in American Jewish history. Selected articles from American Jewish Archives. with an introd. by J.R. Marcus (American Jewish Archives etc., 1971)
1. [With contribs of J.R. Marcus, A.V. Goodman, B.W. Korn a.o.]. XII. 296 p.- With index